PEMANFAATAN JARINGAN LORA UNTUK MONITORING KENDARAAN OPERASIONAL PADA INSTALASI PENELITIAN DAN PENGKAJIAN TEKNOLOGI PERTANIAN (IP2TP) KEBUN PERCOBAAN PASAR MIRING BPTP SUMATRA UTARA - Ben My Cardo Simanjuntuk; Fati Gratianus Nafiri Larosa; Asaziduhu Gea (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2022)
Balai Pengkajian Teknologi Pertanian (BPTP) North Sumatera has an experimental garden "Pasar Miring" that is useful for academic activities, both practicum and research, installation of VUB (Varitas Unggul Baru) rice seed propagation for specific location, assessment and agricultural development. Currently official vehicles operating are 3 units, and the experimental garden area is approximately 15 hectares. Thus the administrator has difficulty knowing the position of the official vehicle during working hours due to the absence of technology that can be used by the office. So to find out the position of the official vehicle when operating, and for vehicle safety from criminal acts and also to avoid misuse of official vehicles. The propose of this paper is a monitoring system for official vehicle by using a desktop application and using Lora (Long Range) Frequency. Lora RFM95 transmitter is placed on the official vehicle and the Lora RFM95 Receiver will be set on the laptop. Lora can send the location of the official vehicle to the desktop application by Internet of Things (IoT) concept via the internet network.